The Use of LanguageTool in Aufsatz I Course to Support Writing Skills of Students at State University of Malang - Kartyco Muhammad Kemal; Sawitri Retnantiti (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2023)
The purpose of this study was to describe the use and response of students to writing skill in the Aufsatz I course using the LanguageTool platform. The method used is descriptive qualitative and the data were obtained from observation and questionnaires sheets. Based on the research results, students are active and enthusiastic while accessing LanguageTool. This platform is easy to access for free and easy to use. Overall, LanguageTool receive a positive response from students. LanguageTool can be used as an alternative medium for self-study in practicing German writing skill. Almost all of students get the feedback on spelling and grammar, while vocabulary requires a premium version to access it. In addition to spelling and grammar, students get feedback on punctuation marks. The deficiency of this platform it requires an internet network to access it and there are still students who experience problems related to this. In addition, there are still errors such as no error detected, no explanation on feedback, incorrect feedback, and error mapping that does not fit the category in LanguageTool.